Implementasi Metode Demonstrasi pada Mata Pelajaran Pendidikan Agama Islam (PAI) untuk Meningkatkan Hasil Belajar Siswa Kelas VIII SMP Budi Utomo Srono Tahun Pelajaran 2023-2024 - Afrida Nur Laili; Zulfikar Ahmad (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
This study aims to analyze the implementation of the demonstration teaching method in improving the learning outcomes of Islamic Religious Education (IRE) for eighth-grade students at SMP Budi Utomo, Srono. The demonstration teaching method was chosen because it provides students with direct experience, allowing them to understand the material more clearly and practically. This research employs a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation, and were then analyzed by systematically describing the findings based on facts and phenomena observed in the field. The results of the study show that the implementation of the demonstration teaching method was carried out through three main stages: planning, implementation, and evaluation. During the planning stage, the teacher prepares relevant materials and teaching aids for the topic being taught. The implementation stage involves using visual media and teaching aids to clarify the explanation of the material, while engaging students in the demonstration activities directly. In the evaluation stage, the teacher provides feedback to assess the students' understanding of the material taught. The application of the demonstration method has a positive impact on the students' learning outcomes. The study shows that students experienced an increase in their understanding of IRE material, greater enthusiasm for learning, and improved responsiveness to issues in their surrounding environment. Additionally, group learning activities during the teaching process strengthened communication skills among students. Therefore, this method proves to be effective in enhancing the quality of classroom learning.